Modifikasi Struktur Eugenol Menjadi Etil 2-(4-Alil-2-Metoksifenoksi) Asetat Melalui Reaksi Alkilasi dengan Etil Kloroasetat - Agistya, Hamida Azza; Fadlan, Arif; Masitoh, Heni (Universitas Tidar, 2025)
Eugenol, a natural product with broad and promising biological activity, possesses three reactive functional groups of hydroxyl, allyl, and methoxy, which can be transformed through chemical reactions into various derivatives. The reaction of eugenol and ethyl chloroacetate with a mole ratio of 1:1 has been reported to produce an alkylation product. However, the use of dry acetone as a solvent and the reflux condition for 12 hours were the drawbacks of this reaction. The structural modification of eugenol into ethyl 2-(4-allyl-2methoxyphenoxy) acetate as an alkylation product was further studied in this paper. The alkylation reaction of eugenol and ethyl chloroacetate was performed in dimethylformamide with a mole ratio of 6:10 (method A), 1:1 (method B), 1:4 (method C), and 1:4 (method D) at room temperature (methods A and D) and under reflux conditions (methods B and C). The results showed that the alkylation reaction with a mole ratio of 1:4 at room temperature (method D) produced ethyl 2-(4-allyl-2-methoxyphenoxy)acetate as a pure compound with a yield of 94%. The structure of the alkylation product was determined by FTIR, NMR spectroscopy, and mass analysis. Ethyl 2-(4-allyl-2-methoxyphenoxy)acetate is a key compound in the development of various eugenol-derived active compounds.